Clusters of Local Bond-Orientational Order in Liquid Gallium: Studies of ab initio and Classical MD Simulations - Chen, Lin-Yuan; Wu, Ten-Ming (My University, 2018)
The structure of liquid Ga at ambient pressure (AP) were generated separately via ab initio and classical molecular dynamics simulations, and analysed with a cluster approach developed in terms of the local bond-orientational order (LBOO) parameters. Two types of cluster structures were found in both simulated liquids, one typified by sixfold orientational symmetry and the other showing fourfold orientational symmetry: The static structure factors (SSF) of the former are akin to that of the hard-sphere (HS) fluid; however, the SSFs of the latter display either an asymmetric first peak with a shape different from that of the HS fluid or even a shoulder on the high-q side of the first peak, similar as the anomalous SSF of liquid Ga at AP.